2018
DOI: 10.3390/f9090511
|View full text |Cite
|
Sign up to set email alerts
|

Species Richness of the Family Ericaceae along an Elevational Gradient in Yunnan, China

Abstract: Knowledge about how species richness varies along spatial and environmental gradients is important for the conservation and use of biodiversity. The Ericaceae is a major component of alpine and subalpine vegetation globally. However, little is known about the spatial pattern of species richness and the factors that drive that richness in Ericaceae. We investigated variation in species richness of Ericaceae along an elevational gradient in Yunnan, China, and used a variation partitioning analysis based on redun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…The latitudinal diversity gradient (i.e., the decrease of species richness with increasing latitude) is one of the most conspicuous and robust biogeographic patterns (Rosenzweig, 1995;Hillebrand, 2004). Previous studies have shown that the northern limits of species distributions in North America are associated with low temperature in winter (Huntley et al, 1989;Zanne et al, 2014; hereafter minimum winter temperature or minimum temperature), which is often measured as the average minimum temperature of the coldest month (e.g., Hawkins et al, 2014) or the average overall temperature of the coldest month (e.g., Chen et al, 2018;Wang et al, 2018;Chen and Su, 2020). These two measures of minimum temperature are often nearly perfectly correlated (e.g., r = 0.996 in data from WorldClim for North America, www.worldclim.org).…”
Section: Introductionmentioning
confidence: 99%
“…The latitudinal diversity gradient (i.e., the decrease of species richness with increasing latitude) is one of the most conspicuous and robust biogeographic patterns (Rosenzweig, 1995;Hillebrand, 2004). Previous studies have shown that the northern limits of species distributions in North America are associated with low temperature in winter (Huntley et al, 1989;Zanne et al, 2014; hereafter minimum winter temperature or minimum temperature), which is often measured as the average minimum temperature of the coldest month (e.g., Hawkins et al, 2014) or the average overall temperature of the coldest month (e.g., Chen et al, 2018;Wang et al, 2018;Chen and Su, 2020). These two measures of minimum temperature are often nearly perfectly correlated (e.g., r = 0.996 in data from WorldClim for North America, www.worldclim.org).…”
Section: Introductionmentioning
confidence: 99%
“…1 b). Paudel et al 1 and Wang et al 24 explained the least effect of the MDE in the richness pattern of threatened plant species in Nepal and Ericaceae in Yunnan Province, China, respectively. In the present study, the climatic variables were more influential than the MDE, and this phenomenon may have suppressed the MDE.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the MDE states that the diversity in species richness in mountain domains is independent of any environmental gradients and that it represents a "null model" for diversity patterns 21,22 . Some studies have validated the effect of the MDE in the mountains of China [23][24][25] . In the present paper, the effects of temperature, precipitation, PET, DIST, and the MDE responsible for the richness pattern of threatened plants in Sichuan Province were examined.…”
mentioning
confidence: 99%
“…3) with centers of diversity and abundance in the temperate south-west and south-east forests, shrublands and montane regions (https://www.ala.org.au/), characterized by impoverished soils (Rossel and Bui, 2016;Kooyman et al, 2017). In Yunnan, China, ericaceous species richness, which includes many Rhododendron species, shows a unimodal relationship with mean annual temperature and mean annual precipitation, and the elevational pattern of species richness is shaped by the combined effects of climate and competition (Wang et al, 2018). Zhang et al (2018) analyzed nutrient concentrations in 32 Ericaceae from 161 sites across southern China, from 27 m to 4906 m above sea level, none of which qualify as cold tundra or boreal forest habitats, and only some were associated with montane areas, all of which Tedersoo et al (2020) consider major habitats for Ericaceae.…”
Section: On Ericaceaementioning
confidence: 99%